Voting on labour-market integration and education policy when citizens differ in mobility and ability - Alexander Haupt; Silke Uebelmesser (Center for Economic Studies and ifo Institute (CESifo), 2009)
We analyse how institutional and political decisions are intertwined. Citizens who differ in their mobility and ability vote first on labour market integration and afterwards on education policy. The institutional decision on integration influences the succeeding education policy. More surprisingly, the prospect of voting on education policy also affects the preceding integration decision. There are incentives for citizens to vote strategically for the institutional setting in which their preferred education policy is more successful at the polls. We show how a 'joint' analysis of the institutional and political decision alters the results compared to an 'isolated' analysis of either of the two decisions. Also, we explore how the two-dimensional heterogeneity of the citizens shapes the voting equilibrium in our setting with sequential voting.
Keywords: D72; F22; H52; I28; 330; Voting; labour-market integration; education policy; migration; Arbeitsmarkt; Wirtschaftsintegration; Bildungspolitik; Wahlverhalten; Public Choice; Internationale Arbeitsmobilität; Qualifikation; Theorie